EFEKTIVITAS STRATEGI PROBLEM FOCUSED COPING DAN EMOTION FOCUSED COPING DALAM MENINGKATKAN PENGELOLAAN STRES SISWA DI SMA NEGERI 1 BARRU - Bakhtiar, Muhammad Ilham; Asriani, Asriani (Universitas Muhammadiyah Metro, 2015)
Abstract. The study aims to determine the effectiveness of the strategy Problem Focused Coping and Emotion Focused Coping in improving stress management SMA Negeri 1 Barru. This research is a quantitative model of pre-experimental pre-test post-test group design .. one sample was 22 people, with purposive sampling techniques. The results showed that the highest percentage obtained after administration of PFCs by 42% which is the highest category, namely the interval 104-114 and strategies EFC scored the highest percentage obtained by 38% which is the highest category, namely the interval 118-125. Hypothesis test results are known to test value t = 0.004 and tt = 2.013 it is seen that the value to <tt value at a significance level of 5%. This means that an increase in stress management through the EFC. The conclusion that the strategy Problem Focused Coping and Emotion Focused Coping effective in improving stress management students at SMA Negeri 1 Barru.Keywords: problem-focused coping, emotion focused coping,stress management